LIMNOLOGICAL STUDY OF DIYALA RIVER, IRAQ - & et al., Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was conducted to evaluate the physicochemical and biological (epiphytic algae) properties of Diyala river. Eighteen environmental parameters were selected in addition to the qualitative study of epiphytic algae (total number of algae and chlorophyll a). Two macrophytes (Phragmites australis and Certatophyllum demersum) were selected for the benthic study. The results showed that the river was alkaline, very hard, brackish water and good aerated. The trophic level is ranged from oligotrophic to mesotrophic according to the results of total phosphorus, total nitrogen, and chlorophyll a. The study revealed that the upper part of the river differed in its properties from the middle and the lower part in the environmental characteristics and the Algal benthic quantities.